Aturan Cramer dalam Aljabar Maks-Plus Interval - Siswanto, Siswanto (Institut Teknologi Bandung, 2015)
Dalam paper ini dibahas aturan Cramer yang dapat digunakan untuk menyelesaikan suatu sistem persamaan linear dalam aljabar maks-plus interval berbentuk . Misalkan himpunan semua bilangan real dan dengan Aljabar maks-plus adalah himpunan dilengkapi dengan operasi (maksimum) dan (plus). Telah dibahas tentang aturan Cramer untuk menyelesaikan sistem persamaan linear dalam aljabar maks-plus. Dari himpunan dapat dibentuk himpunan yaitu himpunan yang anggotanya merupakan interval-interval tertutup dalam . Himpunan yang dilengkapi dengan operasi (maksimum) dan (plus) disebut aljabar maks-plus interval. Kata kunci : Aturan Cramer, Aljabar maks-plus interval.Cramer's Rule in Interval Max-Plus AlgebraAbstract This paper discusses Cramer's rule that can be used to solve a system of linear equations in interval max-plus algebra . Let be the set of real numbers and with Max-plus algebra is the set that is equipped with operations (maximum) and (plus). It has been discussed about Cramer's rule to solve a systems of linear equations in the max-plus algebra. From the set can be formed the set , the set whose members are closed intervals in . The set equipped with operations (maximum) and (plus) is called interval max-plus algebra. Keywords : Cramer's rule, Interval max-plus algebra.